(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Memory, attention, and cognitive dysfunction are psychopathological conditions which most commonly occur after menopause. Different clinical studies revealed a shred of substantial evidence that oxidative stress and estrogen are interlinked in various cognitive dysfunction, including memory impairment, age-related dementia, and Alzheimer’s disease. There is a higher chance of developing cardiovascular disease after menopause. Sharp declines in concentrations of circulating estradiol and estrone are associated with menopause. Estrogen replacement therapy (ERT) enhances the blood circulation to the hippocampus and cortex, providing the optimum environment for the growth and survival of cholinergic neurons. Hence, it improves hippocampal neuron density and ultimately contributes to synaptic plasticity in the hippocampus enhances short and long-term memory. In this study, we assessed memory, attention, and cognition function between pre- and post-menopausal groups. After preliminary screening and applying exclusion criteria, fifteen premenopausal women and fifteen postmenopausal women were finally selected. Different neuropsychological tests such as logical memory test, digit span test, letter cancellation test, trail making test and Stroop test were performed to evaluate the memory, attention, and cognition status. Blood estradiol level was also assessed by using commercial kits. Significant difference (p<0.05) was found in LM-II in logical memory test, digit span test (backward), letter cancelation test, TMT-B in trail making test, the score of part C in stroop test between premenopausal and postmenopausal women. Serum oestradiol concentration (pg/ml) was significantly lower (p<0.001) in postmenopausal women (44.18±10.52) than premenopausal women (175.48 ± 43.20). The current study demonstrates the memory decline and cognitive dysfunction in postmenopausal women and there is a significant difference in estradiol level between pre and postmenopausal women. Estrogen has many neurotrophic actions in the brain and helps to improve memory and cognition. Therefore, estrogen replacement therapy, dietary supplements or a drug having an agonistic effect on estrogen receptors might improve the status of memory, attention, and cognitive function in postmenopausal women. Bangladesh Pharmaceutical Journal 24(1): 26-32, 2021